Sains Memasak Akuntansi: Pemikiran Udayana dan Tri Hita Karana - Ari Kamayanti (Jur. Akuntansi, Politeknik Negeri Malang, 2015)
abstractThis article aims to raise awareness that accounting research needs ought to be based upon beliefs about what is